Biological subtypes of triple-negative breast cancer are associated with distinct morphological changes and clinical behaviour - Elsawaf, Zeinab; Sinn, Peter; Rom, Joachim; Lorenzo Bermejo, Justo; Schneeweiss, Andreas; Aulmann, Sebastian (The breast, 2013)
Abstract: Triple negative breast cancer (TNBC) is a heterogeneous group of tumours accounting for approximately 10-20% of all breast carcinomas. To identify biologically distinct subgroups of TNBC and to assess their clinical properties we examined a series of 142 consecutive patients all of which had received adjuvant cytotoxic chemotherapy using a comprehensive panel of immunostains. Hierarchical unsupervised cluster analysis based on the expression of 13 markers permitted separation of four distinct groups (basal A, basal B, basoluminal, luminal) with the main distinguishing features being cytokeratin (Ck5/6, Ck14, Ck19), EGFR, p53, p16, and Ki-67 expression. Clusters differed with respect to patient age, modified Bloom and Richardson grading, the presence of tumour necrosis, growth pattern and survival, both in uni- and multivariate analysis. Basal (A or B) tumours showed a substantially better outcome compared with basoluminal and luminal tumours. Our data underline the heterogeneity of TNBC and characterise potentially relevant biological subtypes.